2008
DOI: 10.1901/jaba.2008.41-417
|View full text |Cite
|
Sign up to set email alerts
|

Using Performance Feedback to Improve Treatment Integrity of Classwide Behavior Plans: An Investigation of Observer Reactivity

Abstract: The current study replicated the positive effects of performance feedback on treatment integrity and extended previous work by examining reactivity using a multiple baseline design with alternating treatments for observer-present and observer-absent conditions on teachers' implementation of a classwide behavior plan. No differences were found between conditions, and treatment integrity improved across all teachers, suggesting that performance feedback, rather than observer reactivity, was responsible for repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 8 publications
4
54
1
Order By: Relevance
“…Performance feedback, delivered in a variety of different formats, has been shown to effectively improve teachers' and interventionists' treatment implementation of school-based interventions. Daily performance feedback following deteriorating intervention implementation has been demonstrated effective for rapidly improving implementation (Codding, Livanis, Pace, & Vaca, 2008;DiGennaro, Martens, & Kleinmann, 2007;DiGennaro, Martens, & McIntyre, 2005;Noell, Witt, Gilbertson, Ranier, & Freeland, 1997;Witt et al, 1997). Additionally, less frequent performance feedback (e.g., biweekly, weekly; Codding, Feinburg, Dunn, & Pace, 2005;Mortenson & Witt, 1998, respectively) has also been demonstrated as effective for increasing treatment integrity.…”
Section: Procedures For Increasing Treatment Integritymentioning
confidence: 99%
“…Performance feedback, delivered in a variety of different formats, has been shown to effectively improve teachers' and interventionists' treatment implementation of school-based interventions. Daily performance feedback following deteriorating intervention implementation has been demonstrated effective for rapidly improving implementation (Codding, Livanis, Pace, & Vaca, 2008;DiGennaro, Martens, & Kleinmann, 2007;DiGennaro, Martens, & McIntyre, 2005;Noell, Witt, Gilbertson, Ranier, & Freeland, 1997;Witt et al, 1997). Additionally, less frequent performance feedback (e.g., biweekly, weekly; Codding, Feinburg, Dunn, & Pace, 2005;Mortenson & Witt, 1998, respectively) has also been demonstrated as effective for increasing treatment integrity.…”
Section: Procedures For Increasing Treatment Integritymentioning
confidence: 99%
“…T-test analyses suggested that the amount of time used for praising students, asking questions, and accepting student ideas was higher in the observer present condition. In another experimental study, Codding, Livanis, Pace, and Vaca (2008) found no differences between the observer present versus not present conditions regarding the implementation of a classroom behavior management plan for students with disorders. The evidence based on experimental studies therefore does not point clearly in one direction.…”
Section: Measuring Reactivity Through Approaches Other Than Teacher Rmentioning
confidence: 89%
“…In the complex situation of teaching it is not easy to succeed in actually achieving the two intended experimental conditions. In the study of Codding et al (2008), for example, the observer absent condition was simulated by positioning the observer behind a one-way window. As the teachers saw the window, it can be challenged whether they really felt that the observer was absent.…”
Section: Measuring Reactivity Through Approaches Other Than Teacher Rmentioning
confidence: 99%
“…However, the current studies did not include performance feedback; thus, they fall into a small group of studies that have shown that goal setting alone can alter behavior in meaningful ways. This finding has particular clinical importance because the delivery of performance feedback, which is known to be effective in improving treatment adherence, is often resisted due to the time, effort, and costs required to provide it (Cochrane & Laux, 2008;Codding, Livanis, Pace, & Vaca, 2008;Hagermoser Sanetti, Luiselli, & Handler, 2007;Perepletchikova, Hilt, Chereji, & Kazdin, 2009). …”
Section: Discussionmentioning
confidence: 99%